Kaitse suurte ravikulude eest Tšehhis, Eestis ja Lätis: kolm kõrge sissetulekutasemega riiki – kolm erinevat kogemust - Thomson, Sarah; Evetovits, Tamás; Cylus, Jonathan (Eesti Arst, 2018)
Eesti Arst 2018; 97(6):301–304